2015
DOI: 10.3168/jds.2014-8939
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Mycobacterium bovis ssp. caprae in high-temperature, short-term pasteurized pilot-plant milk

Abstract: Experiments to determine the efficacy of high temperature, short time (HTST) pasteurization of milk in terms of inactivation of pathogenic microorganisms were mainly performed between 1930 and 1960. Among the target organisms were Mycobacterium bovis and Mycobacterium tuberculosis. As a result, the Codex Alimentarius prescribes that HTST treatment of milk should lead to a significant reduction of pathogenic microorganisms during milk pasteurization. Due to the development of improved methods for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…However, when we heated BCG cells to 55 or 70 C for 45 s, the BCG inactivation rate was significantly higher than that when cells were heated to 25 C (Figure 8(C,D)). Our results were consistent with a previous studies about the thermal inactivation of pathogenic microorganisms such as M. bovis, M.tuberculosis and M. paratuberculosis during milk pasteurization [22,36]. These studies describe that a high-temperature, short-time (HTST) treatment of milk led to a significant reduction of the target organisms.…”
Section: Discussionsupporting
confidence: 93%
“…However, when we heated BCG cells to 55 or 70 C for 45 s, the BCG inactivation rate was significantly higher than that when cells were heated to 25 C (Figure 8(C,D)). Our results were consistent with a previous studies about the thermal inactivation of pathogenic microorganisms such as M. bovis, M.tuberculosis and M. paratuberculosis during milk pasteurization [22,36]. These studies describe that a high-temperature, short-time (HTST) treatment of milk led to a significant reduction of the target organisms.…”
Section: Discussionsupporting
confidence: 93%
“…Comparison of the generated data with those in the study of Hammer et al (2015) indicates a higher inactivation of M. bovis and Mycobacterium caprae (>18 log 10 -steps) during HTST treatment of milk than for C. burnetii (>10 log 10steps). This comparatively higher heat resistance is in agreement with the demand, that inactivation of C. burnetii should be the internationally accepted performance criterion for milk pasteurization (Codex Alimentarius, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…This partly exceeds the requirements of the Codex Alimentarius. Considering the current pasteurization regimes, Hammer et al (2015) demonstrated an 18 log 10 -step reduction of the highly heat-resistant bacterium Mycobacterium bovis (ssp. bovis and caprae ).…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary inspections are not conducted on home slaughtered carcasses, hence the risk of animal diseases entering the human food chain is higher than in commercially slaughtered livestock. However, heat-treated milk by boiling and thorough cooking of meat products assists with TB control as heat kills the mycobacteria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%